Изучение накопления состава макро- и микроэлементов в лиофизированном экстракте из кореневищ с корнями Plantago altissima L. - Еренко, Е. К.; Хортецкая, Т. В.; Смойловская, Г. П.; Малюгина, Е. А.; Yerenko, O. K.; Khortetska, T. V.; Smoylovska, G. P.; Maliuhina, O. O.; Єренко, Олена Костянтинівна; Хортецька, Тая Володимирівна; Смойловська, Галина Павлівна; Малюгіна, Олена Олександрівна (My University, 2021)
Цель исследования-определение качественной структуры и количественного состава лиофилизированного экстракта, макро- и микроэлементов, полученных из корня Plantago altissima L. Исследование проводилось на аппарате ДСФ-8 методом атомно-абсорбционной спектроскопии. Установлено наличие 15 элементов, среди которых в сиропе преобладали калий, кальций, магний, ферум, алюминий.The purpose of the study was a lyophilized extract from the rhizomes with roots of Plantago altissima L. Determination of the quality structure and quantitative composition of macro- and microelements was performed on the device DSF-8 by atomic absorption spectroscopy. The presence of 15 elements was established, among which in the syrup prevailed in the amount of potassium, calcium, strength, magnesium, ferum and aluminum.
Study of accumulation of macro- and microelements in a lyophilized extract of Platango altissima L. roots
Keywords: подорожник большой; растительное сырье; макроэлементы; микроэлементы; лиофилизованный экстракт; large plantain; vegetable raw materials; macroelements; microelements; lyophilized extract